2012
DOI: 10.7903/cmr.11048
|View full text |Cite
|
Sign up to set email alerts
|

Job Empowerment and Customer Orientation of Bank Employees in Kuching, Malaysia

Abstract: Customer orientation and empowerment of bank employees is investigated, sample is 225 respondents. Methodology employed is descriptive, factor, correlation and regression analysis. Findings show autonomy, job constraint, education and seniority is significant empirically validating job empowerment as a factor. A customer-orientated culture leads to excellent customer services. Limitations; sample size, one industry focus and no interactive effects. Recommendations include other service industries, comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The results showed that structural empowerment positively and significantly affects organizational commitment. Empowerment has received significant attention from scholars and practitioners due to its impact on organizational effectiveness and competitive advantage in the service industry (Kassim et al, 2012). Structural empowerment is a management practice and policy that aims to provide power from management to staff, focusing on practical management and policies.…”
Section: Organizational Support Affects Structural Empowermentmentioning
confidence: 99%
“…The results showed that structural empowerment positively and significantly affects organizational commitment. Empowerment has received significant attention from scholars and practitioners due to its impact on organizational effectiveness and competitive advantage in the service industry (Kassim et al, 2012). Structural empowerment is a management practice and policy that aims to provide power from management to staff, focusing on practical management and policies.…”
Section: Organizational Support Affects Structural Empowermentmentioning
confidence: 99%
“…Despite its importance within the dimensions of the psychological climate framework and its influence as an individual and work resource, autonomy is sometimes confused with empowerment, with the terms used interchangeably (Kassim et al, 2012). Within the parameters of this study, autonomy and empowerment are considered separate values as identified by Goodman et al (2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…SE refers to organizational policies, practices and structures (largely HRM practices) that empower employees to make decisions at work (Kassim et al , 2012; Mills and Ungson, 2003). It involves practices of power sharing with employees at lower hierarchical levels to make decisions and for accountability (Zeglat et al , 2014; Cho and Faerman, 2010).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In this sense, the empowerment of call centers’ employees, and the implication of autonomy and knowledge about work-related situations, may increase their sense of responsibility and capacity to better respond to customer needs (Kim, 2007; Ayupp and Chung, 2010; Kassim et al , 2012; Shahril et al , 2015; Proença et al , 2017). According to Ongori (2009) and Isimoya and Bakarey (2013), it is important to allow contact employees to have the autonomy, self-control and job discretion to achieve the efficiency and effectiveness of services.…”
Section: Customer Satisfaction Empowerment and Job Satisfactionmentioning
confidence: 99%